Philippine-Japan Bilateral Agreements: Analysis of Possible Effects on Unemployment, Distribution and Poverty in the Philippines Using CGE-Microsimulation Approach - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 2004)
The paper employs an integrated CGE-microsimulation approach to analyze the possible effects of the Philippine-Japan bilateral agreements on unemployment, income distribution and poverty. The results indicate contraction in agriculture but expansion in industry, particular in the nonfood manufacturing sector. Factor prices drop in agriculture while increase in industry. Unemployment in agriculture deteriorates while in industry improves. Thus income inequality worsens. However, poverty improves, but the improvement is much higher in the National Capital Region (NCR) than in other areas, especially rural. NCR has the least poverty incidence while rural has the highest. The generally favourable poverty effects are due to the overall increase in household income and the reduction in consumer prices.
Keywords: 330; unemployment; computable general equilibrium (CGE); poverty; microsimulation; foreign trade; bilateral agreements; distribution; Philippines; Internationales Abkommen; Handelsliberalisierung; Arbeitslosigkeit; Einkommensverteilung; Armut; Allgemeines Gleichgewicht; Philippinen; Japan; Wirkungsanalyse; CGE-Modell